Analisis Kemacetan Lalu Lintas Sepanjang Jalan Z.A. Pagar Alam Dengan Metode Manual Kapasitas Jalan Indonesia (Studi kasus segmen Universitas Lampung sampai dengan Mall Boemi Kedaton) - Novitasari, Shartyka; Martono, Yohanes; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Road facilities aim to accomodate existing traffic volumes the designing is also adjusted to traffic characteristic. However, in fact, the comfort level has not meet the requirements of the guide book. This problem is indicated by the slowing down of passing vehicles, the long traffic jam that makes road density this research, simulated to compare vehicles volume and the road capacity along the research road, analysis the level of service catagory based on the road density, predicted the time traveled of the traffic and accomodated by types of road, degree of saturation and speed allowed.  Based on the date analysis the highest traffic jam for traffic volume is in Purnawirawan, then after the analysis of capacity, the highess road density is in University of Lampung, the underpass project for the degree of saturation the analysis is compared with the on the spot real time date. And the result is the highest traffic jam is in underpass project in University of Lampung wich is the real time distance traveled is more density than the distance allowed.  In conclusion, we need to review the geometric design of road, because the geometric design of road is really affect traffic jam. And we have to re-announced about public transportation, so the vehicles volume will decrease. Keywords: traffic volumes. Degree of saturation, speed, road capacity..